Analisis Komparatif Indeks Saham Syariah Indonesia (ISSI) Sebelum dan Saat Implementasi Kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) di Indonesia - Citradewi, Adelina (AKTSAR: Jurnal Akuntansi Syariah, 2021)
This study aims to determine the comparison of the Islamic stock index before and during the implementation of the PPKM policy in Indonesia. The approach used in this study is a quantitative approach. The data in this study are secondary data that comes from the Indonesia Stock Exchange website. The research population is companies that are included in the Indeks Saham Syariah Indonesia (ISSI). The Wilcoxon Signed Rank Test was used to test the research hypothesis. The results show that there is an increase in the sharia stock index during the implementation of the PPKM policy and there is a significant difference between the sharia stock index before and during the implementation of the PPKM policy.Kata kunci: Saham syariah; Indeks saham; PPKM; ISSI